Anoxic sediments off Central Peru record interannual to multidecadal changes of climate and upwelling ecosystem during the last two centuries - D. Gutiérrez; A. Sifeddine; J. L. Reyss; G. Vargas; F. Velazco; R. Salvatteci; V. Ferreira; L. Ortlieb; D. Field; T. Baumgartner; M. Boussafir; H. Boucher; et al. (Advances in Geosciences, 2006)
High-resolution paleo-environmental and paleo-ecological archives in laminated sequences are present in selected areas from the upper continental Peruvian margin within the oxygen minimum zone. We present initial results of a multidisciplinary study (the PALEOPECES project) that aims to reconstruct environmental and ecosystem variability during the past 200 years from high-resolution records. We report chronology development, sediment structure, elemental, organic, and mineralogical compositions of a box core collected at 300 m depth off Pisco, central Peru. An average sedimentation rate of 2.2 mm y-1 was estimated from downcore excess 210Pb activities for the last 100-150 years. Extending this rate further downcore indicates that a slump located at 52 cm depth from the top of the core can be correlated with a large tsunami that struck the coast of central Peru in 1746. X-ray analyses reveal laminated structures composed of couplets of light and dark laminae. Observations under polarized microscope show that light laminae are dominated by more dense, detrital and terrigenous material, while dark laminae are less dense with greater concentrations of amorphous biogenic silica. Downcore variations in dry bulk density and X-ray radioscopy of gray level show similar patterns, including a major shift at 34 cm depth (ca. mid-nineteenth century). A finely laminated sequence, which may include annual varves, is present between 34 cm depth and the slump layer. Sediment characteristics of the sequence suggest increased seasonality of terrigenous versus biogenous sedimentation during the corresponding period. In addition to a mid-nineteenth century change and considerable multidecadal variability in TOC, there is a positive trend in the past 50 years. Mineralogical analyses from a Fourier Transformed Infrared Spectroscopy (FTIR) of the upper core covering the last 25 years, indicate higher concentrations of the mineral fraction (quartz, feldspar, kaolinite and illite) in layers including large El Niño events (1982-1983, 1986-1987 and 1997-1998), with the largest peak during the 1997-1998 episode. These results confirm that anoxic sediments off Pisco are suitable archives to investigate interannual and decadal changes in oceanographic conditions and climate of the northern Humboldt upwelling system.